2001
DOI: 10.1002/hbm.1059
|View full text |Cite
|
Sign up to set email alerts
|

Vascular responses to syntactic processing: Event‐related fMRI study of relative clauses

Abstract: Event-related functional magnetic resonance imaging was used to investigate the localization of syntactic processing in sentence comprehension. Matched pairs of sentences containing identical lexical items were compared. One member of the pair consisted of a syntactically simpler sentence, containing a subject relativized clause. The second member of the pair consisted of a syntactically more complex sentence, containing an object relativized clause. Ten subjects made plausibility judgments about the sentences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
74
2
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 131 publications
(81 citation statements)
references
References 46 publications
4
74
2
1
Order By: Relevance
“…Most of this work has implicated left anterior frontal brain regions, specifically including Broca's area, in the processing of sentences with complex structure (Ben-Shachar et al, 2003;Caplan et al, 1998Caplan et al, , 1999Caplan et al, , 2001Cooke et al, 2001;Dapretto and Bookheimer, 1999;Friederici et al, 2000;Grossman et al, 2002;Heim et al, 2003;Inui et al, 1998;Just et al, 1996;Musso et al, 2003;Newman et al, 2001;Ni et al, 2000;Sakai et al, 2001;Stromswold et al, 1996;Waters et al, 2003;Wartenburger et al, 2004). In general, conclusions drawn from this research fit well with behavioral and lesion evidence gleaned over decades about the role of left inferior frontal cortex (L-IFC) including Broca's area.…”
Section: Introductionsupporting
confidence: 73%
“…Most of this work has implicated left anterior frontal brain regions, specifically including Broca's area, in the processing of sentences with complex structure (Ben-Shachar et al, 2003;Caplan et al, 1998Caplan et al, , 1999Caplan et al, , 2001Cooke et al, 2001;Dapretto and Bookheimer, 1999;Friederici et al, 2000;Grossman et al, 2002;Heim et al, 2003;Inui et al, 1998;Just et al, 1996;Musso et al, 2003;Newman et al, 2001;Ni et al, 2000;Sakai et al, 2001;Stromswold et al, 1996;Waters et al, 2003;Wartenburger et al, 2004). In general, conclusions drawn from this research fit well with behavioral and lesion evidence gleaned over decades about the role of left inferior frontal cortex (L-IFC) including Broca's area.…”
Section: Introductionsupporting
confidence: 73%
“…These processes involving syntactic working memory are not reflected in a local ERP component but in a sustained left frontal negativity (Fiebach and Friederici, 2003;Fiebach et al, 2001). These latter syntactic processes are supported by BA 44/45 in the IFG (Ben-Shahar et al, 2003;Caplan et al, 1998Caplan et al, , 2002Fiebach et al, 2001;Newman et al, 2003;Stromswold et al, 1996) (indicated by white circle in Fig. 1).…”
Section: Resultsmentioning
confidence: 67%
“…To the best of our knowledge this technique has not been implemented in fMRI experiments before. Previous attempts include the use of behavioural SPR to determine the appropriate duration for a fixed word presentation in fMRI (Caplan et al 2002), or the use of self-paced eye movements as predictors of brain activation (Richlan et al 2014;Bonhage et al 2015). However, in none of these cases were the participants asked to pace the experiment themselves while in the MRI scanner.…”
Section: Discussionmentioning
confidence: 99%